Oxidative stress and antioxidant status among the elderly in Jakarta - Novi Silvia Hardiany; Daniya Qanita Amani; Jasmine Virginia Anjani; Prima Christin Natalia; Rheina Tamara Tarigan (Acta Biochimica Indonesiana, 2024)
Background: Indonesia is experiencing a demographic shift, with the elderly population comprising 9.92% (26.82 million) of the total population, 8.21% of whom reside in Jakarta. Oxidative stress is a key contributor to the development of degenerative diseases associated with aging, while antioxidant defenses can mitigate its effects. Objective: This study aimed to assess oxidative stress levels, measured by malondialdehyde (MDA), and antioxidant status, including catalase, reduced glutathione (GSH), and vitamin C, in the elderly population of Jakarta. Methods: A cross-sectional study was conducted with 91 elderly participants from three sub-districts in Jakarta. Erythrocyte lysate samples were analyzed to measure MDA, catalase, and GSH levels, while plasma was used to measure vitamin C. All parameters were quantified using a spectrophotometer. MDA levels and antioxidant status were categorized based on age, blood pressure, and the number of chronic diseases, with statistical analysis performed using the Kruskal-Wallis test. Results: The median MDA level was 2.68 (1.61–5.64) nmol/mL, with the highest levels observed in participants aged 60–64 and those with three chronic diseases. The mean catalase level was 2.41 ± 0.39 U/mL, the median GSH level was 6.16 (2.02–128.07) µmol/mL, and the mean vitamin C level was 10.87 ± 4.9 µg/mL. No significant differences in antioxidant status were observed based on age, blood pressure, or the number of chronic diseases. Conclusion: Oxidative stress is prevalent in the elderly and is particularly influenced by the presence of multiple chronic diseases. However, antioxidant status does not significantly vary with age, blood pressure, or disease burden in this population.